2006
DOI: 10.1007/bf02985588
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in the hemodynamics of the femoral head as evaluated by early phase of bone scintigraphy

Abstract: The present study demonstrated that blood flow and blood pool of the femoral head decrease with aging particularly in women. This hemodynamic deterioration of the femoral head caused by aging may have an effect on the onset and progression of hip disorders by influencing bone metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Bridgeman and Brookes (1996) reported marrow ischemia in femoral diaphyses of aged women and men and a greater reliance upon the periosteal blood supply (i.e., centripetal blood flow) for survival of the diaphyseal cortex [30]. Conversion of diaphyseal flow from centrifugal in youth to centripetal in old age represents an abnormal blood flow pattern [36] and corresponds with declines in bone perfusion reported in animal models and humans [6, 7, 33, 3739]. Diminished blood flow to bone marrow [6, 7, 33, 40] and bone [6, 7], reduced vasodilator capacity of bone arteries [6, 7], diminished bone volume [6, 7] and mineral density [40], and replacement of hematopoietic marrow with adipocytes [26, 33, 40] have been reported in aged rats and humans.…”
Section: Discussionmentioning
confidence: 99%
“…Bridgeman and Brookes (1996) reported marrow ischemia in femoral diaphyses of aged women and men and a greater reliance upon the periosteal blood supply (i.e., centripetal blood flow) for survival of the diaphyseal cortex [30]. Conversion of diaphyseal flow from centrifugal in youth to centripetal in old age represents an abnormal blood flow pattern [36] and corresponds with declines in bone perfusion reported in animal models and humans [6, 7, 33, 3739]. Diminished blood flow to bone marrow [6, 7, 33, 40] and bone [6, 7], reduced vasodilator capacity of bone arteries [6, 7], diminished bone volume [6, 7] and mineral density [40], and replacement of hematopoietic marrow with adipocytes [26, 33, 40] have been reported in aged rats and humans.…”
Section: Discussionmentioning
confidence: 99%
“…It is also observed that the total speed and volume of blood in the bone decrease with age, causing marrow pH and pO 2 to fall (Bridgeman and Brookes, 1996). The ratio of blood flow and pooling in the femoral head versus its diaphysis has been identified to fall with age (Hamaguchi et al, 2006). These changes may impact hematopoiesis, impair bone regenerative ability, as well as increase the risk of osteoporosis in older people (Bridgeman and Brookes, 1996;Hamaguchi et al, 2006;Marenzana and Arnett, 2013).…”
Section: Agementioning
confidence: 99%
“…The ratio of blood flow and pooling in the femoral head versus its diaphysis has been identified to fall with age (Hamaguchi et al, 2006). These changes may impact hematopoiesis, impair bone regenerative ability, as well as increase the risk of osteoporosis in older people (Bridgeman and Brookes, 1996;Hamaguchi et al, 2006;Marenzana and Arnett, 2013). Age-related changes in blood vessels and vascular niches impact hematopoietic stem cells (HSCs) (Morrison and Scadden, 2014;Kusumbe et al, 2016;Pinho and Frenette, 2019).…”
Section: Agementioning
confidence: 99%
“…The etiology of ONFH is still unknown, but is associated with trauma, steroid‐induced alcohol abuse, hemoglobinopathy, Gaucher's disease, coagulopathies, Caisson disease, inflammatory or autoimmune diseases, and other idiopathic mechanisms . The pathophysiology of ONFH may include the interruption of blood supply to the extraosseous area and embolism in subchondral blood vessels, which causes venous stasis and increase in femoral head bone marrow pressure …”
mentioning
confidence: 99%
“…5 The pathophysiology of ONFH may include the interruption of blood supply to the extraosseous area and embolism in subchondral blood vessels, which causes venous stasis and increase in femoral head bone marrow pressure. 5,6 There are various treatment methods of ONFH in early stages. [7][8][9][10][11][12][13][14][15][16] The vascularized bone grafting has been demonstrated to achieve better clinical results than nonvascularized bone grafting.…”
mentioning
confidence: 99%